Elaiophores: their taxonomic distribution, morphology and functions - Fiorilo Possobom, Clivia Carolina; Machado, Silvia Rodrigues [UNESP] (Soc Botanica Brasil, 2017)
Elaiophores are floral glands that secrete non-volatile oils as a reward for their pollinators. Their secretions mediate a specialized interaction between oil-producing plants and a few species of oil-collecting bees - Apidae and Melittidae. The present review focuses on the morphological and functional aspects of these secretory structures. We also provide information on their chemistry and pollination ecology. Our survey is organized taxonomically among the plant families for which elaiophore occurrence has been confirmed - for the monocots, Iridaceae and Orchidaceae, and for the eudicots, Calceolariaceae, Cucurbitaceae, Krameriaceae, Malpighiaceae, Plantaginaceae, Primulaceae, Scrophulariaceae, Solanaceae and Stilbaceae. Most oil flowers are zygomorphic, bisexual, nectarless and present their elaiophores on the protective whorls or on the androecium. Trichomal elaiophores are reported in all of these families except Krameriaceae and Malpighiaceae, and they vary in the density and morphology of the trichomes. Epithelial elaiophores occur in some monocot representatives and in Krameriaceae and Malpighiaceae, and are similar among species. An intermediate type of elaiophore is reported in some species of Orchidaceae. Regardless of elaiophore type, these glands have similar subcellular features and secretion-release mechanisms. Finally, we note the dearth of information on elaiophore ultrastructure and functioning for several plant families.
Keywords: Asparagales; bees; Cucurbitales; Ericales; Lamiales; Malpighiales; oil flowers; Solanales; Zygophyllales